Effect of a fast-track nursing pathway for emergency percutaneous coronary intervention on clinical outcomes in patients with acute myocardial infarction - Bai, Cai-Yun; Yang, Ying; Xiao, Hui-Yan; Wang, Jin; Xu, Kai-Yun (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAcute myocardial infarction (AMI) requires prompt revascularization to optimize outcomes. This study aimed to evaluate the effect of a structured fast-track nursing pathway on clinical outcomes in patients undergoing emergency percutaneous coronary intervention (PCI).MethodsThis retrospective cohort study included 324 AMI patients admitted through the emergency department between May 2023 and May 2025. Patients treated prior to the implementation of a fast-track nursing pathway (n = 156) formed the control group, while those treated after pathway implementation (n = 168) formed the observation group. The fast-track pathway included dedicated nursing teams, standardized triage-to-catheterization workflows, expedited monitoring and preparation procedures, and structured patient-family education. Clinical outcomes assessed included time to reperfusion, rescue success rate, left ventricular function [left ventricular ejection fraction (LVEF), left ventricular end-systolic volume (LVESV), and left ventricular end-diastolic volume (LVEDV)], incidence of adverse events, and patient satisfaction.ResultsCompared with the control group, the observation group had significantly shorter resuscitation room time and reperfusion time (p < 0.001), and a higher rescue success rate (94% vs. 79%). By day 3, LVEF improvement was significantly greater in the observation group (p < 0.001). There were no significant differences in LVESV, LVEDV, or adverse event incidence between groups. The observation group reported higher total satisfaction (96.4% vs. 80.1%, p < 0.001).ConclusionsThe fast-track nursing pathway significantly enhanced emergency care efficiency, improved early cardiac recovery, and increased satisfaction without compromising patient safety. These findings support broader adoption of nurse-led process innovations in AMI care.